Climate change–contaminant interactions in marine food webs: Toward a conceptual framework. (21st March 2017) - Alava, Juan José; Cheung, William W. L.; Ross, Peter S.; Sumaila, U. Rashid
Abstract: Climate change is reshaping the way in which contaminants move through the global environment, in large part by changing the chemistry of the oceans and affecting the physiology, health, and feeding ecology of marine biota. Climate change‐associated impacts on structure and function of marine food webs, with consequent changes in contaminant transport, fate, and effects, are likely to have significant repercussions to those human populations that rely on fisheries resources for food, recreation, or culture. Published studies on climate change–contaminant interactions with a focus on food web bioaccumulation were systematically reviewed to explore how climate change and ocean acidification may impact contaminant levels in marine food webs. We propose here a conceptual framework to illustrate the impacts of climate change on contaminant accumulation in marine food webs, as well as the downstream consequences for ecosystem goods and services. The potential impacts on social and economic security for coastal communities that depend on fisheries for food are discussed. Climate change–contaminant interactions may alter the bioaccumulation of two priority contaminant classes: the fat‐soluble persistent organic pollutants (POPs), such as polychlorinated biphenyls (PCBs), as well as the protein‐binding methylmercury (MeHg). These interactions include phenomena deemed to be either climate change dominant (i.e., climate change leads to an increase in contaminant exposure) or contaminant dominant (i.e., contamination leads to an increase in climate change susceptibility). We illustrate the pathways of climate change–contaminant interactions using case studies in the Northeastern Pacific Ocean. The important role of ecological and food web modeling to inform decision‐making in managing ecological and human health risks of chemical pollutants contamination under climate change is also highlighted. Finally, we identify the need to develop integrated policies that manage the ecological and socioeconomic risk of greenhouse gases and marine pollutants. Abstract : A new conceptual framework integrating the threats posed by the interplay between ocean warming, ocean acidification, and chemical pollution in marine food webs is proposed. Climate change–contaminant interaction processes deemed as a climate change dominant, leading to increased sensitivity to pollutant exposure and food web bioaccumulation. Climate change–contaminant interaction processes deemed as a contaminant dominant, leading to increased susceptibility to climate change effects.